Quality control of bagged cement in the bagged factory unit of PT X’s - Rafkie Aulya; Ahmad Syafruddin Indrapriyatna; Ardhian Agung Yulianto (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
PT X is one of the oldest and leading cement producers in Indonesia which was founded on March 18, 1910. In supporting business operations and product marketing using bag/zak packaging, PT X produces bag bags in the Bag Factory Unit. Bag production operations are carried out on 2 production lines. Line III has been operating since 1999 and Line IV in 2010. Production operational data in 2024 shows that there is a difference in the percentage of rejects of 0.43%, where line III production rejects are 0.58% (4.47σ) and line IV is 1.01% (3.95σ). The significance test using the Independent Sample T-Test method obtained a P-Value of 0.026 which means there is a significant difference in the two production lines. The quality control method used is the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) framework, this methodology is based on data and statistics designed to reduce and control process variations. The analysis was conducted by determining priority problems using a Pareto Diagram, analyzing root causes using a Fishbone Diagram, and FMEA (Failure Mode and Effect Analysis) to prioritize improvements based on the Risk Priority Number (RPN) value. The analysis revealed three dominant types of defects: bag folds (33.36%), bag glue (25.99%), and bag valves (21.38%), all of which occurred on the bottomer machine, with an accumulated incidence of 80.74%. The FMEA analysis indicated that the root cause of the problem was caused by suboptimal machine settings and limited operator competence. As a preventative measure, the author created a checklist for operational equipment conditions to ensure proper control of the factors causing product defects. The improvement results showed a 26.33% increase in the sigma value to 4.99σ.